The Development of Teaching Materials with Mind Mapping Methods Literary Literacy Oriented and Character Education to Improve Understanding of Literary History - Dewantara, I Putu Mas; Ade Asih Susiari, Tantri (LPPM Undiksha, 2018)
This study aims to develop teaching materials using mind mapping method oriented to literary and character education in a valid, practical, and effective Literature History course. There are three aspects that used to measure the instructional material developed, namely: 1) the content of teaching materials validity will be assessed by experts that adjusted to the supporting theory while construct validity is assessed by experts by paying attention to the relevance and suitability of the developed teaching materials; 2) practicality of the developed teaching material is measured by its implementation in lectures in class by using the instrument of questionnaire responses of students and lecturers; 3) effectiveness of instructional materials was measured using multiple choice tests. The development of this teaching material follows the procedure for product development from Plomp, namely: 1) initial investigation, 2) design, 3) realization/ construction, 4) test, evaluation, and revision; and 5) implementation. Given the time constraints, this study did not arrive at the implementation stage but only arrived at limited trials. From the results of the study, the instructional material developed has met the criteria of valid, practical, and effective. Whereas from the results of limited trials, the instructional material developed effectively increases the understanding of Literature History in PBSI semester I students in the academic year 2018-2019. This is evident by increasing of the percentage of students getting B +, A-, that is 62% in the first cycle become 80% in second cycle. It is already above the percentage that have been achieved and even exceeding the target, that is 70% of students get B +, A-, and A in the beginning of study.